Understanding molecular level properties of N(n-butyl)-N′-[p-chlorophenoxy) acetyl]urea by density functional, molecular docking and molecular dynamics computations - J. Sunil; K. Srishailam; Thirunavukkarasu Muthu Kumar; G. Ramana Rao (Results in Chemistry, 2025)
Geometry optimization was made for N-(n-butyl)-N′-[(p-chlorophenoxy) acetyl] Urea (BPCAU), employing DFT/B3LYP/6–311++G(d,p) level of theory. The computations revealed the presence of intra-molecular hydrogen bond. Same level of theory was used to obtain equilibrium structure parameters, valence force field (general), vibrational frequencies in the harmonic approximation, potential energy distribution (PED), intensities of infrared and Raman fundamentals, nonlinear optical (NLO) profile, frontier molecular orbital (FMO) characteristics, Natural bond orbital (NBO) properties and Fukui function parameters, for the molecule. Utilizing TD-DFT, absorption maxima (λmax) of electronic transitions for the molecule under investigation computed. Frontier molecular orbital analysis helped to gain deeper insights into the origin of UV–Vis spectrum and chemical reactivity. Fukui function identified centers vulnerable to electrophilic and nucleophilic attacks within the molecule being investigated. The calculated structure parameters and IR spectrum exhibited nice agreement with their corresponding observed parameters. The computations proved that the molecule is not good for NLO applications. The compound showed acceptable toxicity and drug-likeness properties for the ADMET/T testing. The binding ability of the molecule was verified with GRK2 receptor using molecular docking combined with molecular dynamic simulation studies, along with inhibition constant, hydrogen bonding interactions, drug-likeness, biological activity and stability factor.